Negative electrode active material, negative electrode, lithium-ion secondary battery and lithium-ion secondary battery module

JP2026165473APending Publication Date: 2026-10-14AESC JAPAN LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
JP2025057878
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2025-03-31
Publication Date
2026-10-14

Smart Images

  • Figure 2026165473000002
    Figure 2026165473000002
  • Figure 2026165473000001
    Figure 2026165473000001
Patent Text Reader

Abstract

This invention provides a negative electrode active material that enables the creation of lithium-ion secondary batteries with improved performance balance in rapid charging characteristics, energy density, and gas generation suppression. [Solution] The invention comprises graphite powder and Si / C powder containing Si-C composite particles containing silicon and carbon materials, wherein the graphite powder comprises graphite powder (A) and graphite powder (B), and the fracture strength of graphite powder (A), measured in accordance with JIS R 1639-5:2007, is CS A The fracture strength of the graphite powder (B) is CS B In that case, CS A <CS B And CS B / CS A A negative electrode active material whose value is between 3.00 and 6.20.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a negative electrode active material, a negative electrode, a lithium ion secondary battery, and a lithium ion secondary battery module.

Background Art

[0002] Si / C powder is sometimes used as a negative electrode active material. Patent Document 1 discloses composite particles composed of a Si-C composite material, which aim to provide composite particles that achieve high silicon utilization in lithium ion secondary batteries and are less likely to be oxidized when dispersed in water, the composite particles containing a carbon material and silicon, having a silicon content of 30 mass% or more and 80 mass% or less, and having a true density measured by dry density measurement using helium gas of 1.80 g / cm 3 or more and 1.99 g / cm 3 or less, wherein in the Raman spectrum of the composite particles, a peak is present at 450 to 495 cm -1 , the intensity of the peak is defined as I Si , the intensity of the G band (peak intensity near 1580 cm -1 ) is defined as I G , I Si / I G is 1.3 or less, and when the atomic number ratios of Si, O and C determined by the narrow spectra of X-ray photoelectron spectroscopy of the composite particles are respectively defined as A Si , A O , and A C , and among the Si species ratios obtained by Si2p spectrum state analysis, the ratios of SiO2 and SiO are respectively defined as B SiO2 , B SiO , A Si is 0.05 or more, and at least one of the following formulas (1) and (2) is satisfied, the composite particles are disclosed. Y≧0.75 …(1) Y≧-0.32X+0.81 …(2) [In formulas (1) and (2), X=I Si / I G , and Y=A C / (A C+A Si ×(B SiO2 +B SiO )) That is. ] [Prior art documents] [Patent Documents]

[0003] [Patent Document 1] Japanese Patent Publication No. 2023-059283 [Overview of the Initiative] [Problems that the invention aims to solve]

[0004] The present invention provides a negative electrode active material and a negative electrode that can be used to obtain a lithium-ion secondary battery with an improved balance of rapid charging characteristics, energy density, and gas generation suppression, as well as a lithium-ion secondary battery and a lithium-ion secondary battery module with an improved balance of rapid charging characteristics, energy density, and gas generation suppression. [Means for solving the problem]

[0005] The inventors diligently conducted research to solve the above problems. As a result, they found a method comprising graphite powder and Si / C powder containing Si-C composite particles containing silicon and carbon material, wherein the graphite powder comprises graphite powder (A) and graphite powder (B), and the fracture strength of graphite powder (A), measured in accordance with JIS R 1639-5:2007, is CS A The fracture strength of the graphite powder (B) is CS B In that case, CS A <CS B And CS B / CS A We discovered that a negative electrode active material with a value of 3.00 to 6.20 can improve the balance of performance in rapid charging characteristics, energy density, and gas generation suppression of the resulting lithium-ion secondary battery, thus completing the present invention.

[0006] According to the present invention, the following negative electrode active material, negative electrode, lithium-ion secondary battery, and lithium-ion secondary battery module are provided.

[0007] [1] It comprises graphite powder and Si / C powder containing Si-C composite particles containing silicon and carbon materials, The graphite powder includes graphite powder (A) and graphite powder (B). The fracture strength of the graphite powder (A), measured in accordance with JIS R 1639-5:2007, is given by CS. A The fracture strength of the graphite powder (B) is CS B In that case, CS A <CS B And CS B / CS A A negative electrode active material whose value is between 3.00 and 6.20. [2] Said CS A The negative electrode active material described in [1], wherein the pressure is between 5 MPa and 50 MPa. [3] Said CS B A negative electrode active material as described in [1] or [2], wherein the pressure is between 30 MPa and 200 MPa. [4] The negative electrode active material according to any one of [1] to [3], wherein the graphite powder (A) comprises graphite particles that do not contain amorphous carbon on their surface. [5] The negative electrode active material according to any one of [1] to [4], wherein the graphite powder (B) comprises graphite particles containing amorphous carbon on its surface. [6] The content of the graphite powder (A) in the negative electrode active material is W A The content of the graphite powder (B) in the negative electrode active material is W B When that happens, W B / W A A negative electrode active material described in any of [1] to [5], wherein the value of is between 0.50 and 3.00. [7] Median diameter D in the volume frequency particle size distribution of the graphite powder (A) obtained by laser diffraction scattering method 50A negative electrode active material according to any of [1] to [6], wherein the particle size is 0.5 μm or more and 30.0 μm or less. [8] Median diameter D in the volume frequency particle size distribution of the graphite powder (B) obtained by laser diffraction scattering method 50 A negative electrode active material according to any of [1] to [7], wherein the particle size is 1.0 μm or more and 50.0 μm or less. [9] The negative electrode active material according to any one of [1] to [8], wherein the graphite powder comprises artificial graphite particles.

[10] The negative electrode active material according to any one of [1] to [9], wherein the content of the graphite powder in the negative electrode active material is 10.0 parts by mass or more and 99.0 parts by mass or less when the total amount of the negative electrode active material is 100.0 parts by mass.

[11] The negative electrode active material according to any one of [1] to

[10] , wherein the carbon material in the Si-C composite particles includes a porous carbon material, and the silicon is present in at least a portion of the pores of the porous carbon material.

[12] The negative electrode active material described in any of [1] to

[11] , wherein the fracture strength of the Si / C powder measured in accordance with JIS R 1639-5:2007 is 50 MPa or more and 600 MPa or less.

[13] Median diameter D in the volume frequency particle size distribution of the Si / C powder obtained by laser diffraction scattering method. 50 A negative electrode active material according to any of [1] to

[12] , wherein the particle size is 0.5 μm or more and 30.0 μm or less.

[14] The negative electrode active material according to any one of [1] to

[13] , wherein the content of the Si / C powder in the negative electrode active material is 1.0 part by mass or more and 90.0 parts by mass or less when the total amount of the negative electrode active material is 100.0 parts by mass.

[15] The content of the graphite powder in the negative electrode active material is W C The content of the Si / C powder in the negative electrode active material is W SiC When that happens, W SiC / W CA negative electrode active material described in any of [1] to

[14] , wherein the value of is between 0.10 and 10.00.

[16] A negative electrode active material according to any of [1] to

[15] , wherein the energy density E measured by the method 1 below is 875 Wh / L or more on a cell basis. (Method 1) A slurry of the negative electrode active material is prepared by adding an appropriate amount of water to a solid component consisting of 96.9 parts by mass of the negative electrode active material, 0.1 parts by mass of single-walled carbon nanotubes, and 3.0 parts by mass of polyacrylic acid. Next, the slurry of the negative electrode active material is applied to the copper foil, which is the negative electrode current collector, so that the initial charge capacity per unit area is 4.3 mAh / cm². 2 After coating with an amount such that the negative electrode current collector and negative electrode active material layer are used, the material is dried to obtain a negative electrode laminate having the negative electrode current collector and the negative electrode active material layer. Next, the negative electrode laminate is pressed using a roll press to obtain a negative electrode laminate with a density of 1.65 g / cm³ of the negative electrode active material layer. 3 The negative electrode is obtained by pressing with pressure such that the following occurs. Next, the negative electrode and lithium nickel cobalt manganese oxide (Li(Ni 0.9 Co 0.05 Mn 0.05A lithium-ion secondary battery is manufactured by placing an electrode laminate, in which a positive electrode containing 0.2V (O2) and a non-aqueous electrolyte are positioned opposite each other via a polyethylene separator, and placing these two electrodes together in a laminate casing molded from an aluminum-based film. Positive electrode tabs and negative electrode tabs are connected to the negative electrode and positive electrode, respectively, and the laminate casing is sealed. The lithium-ion secondary battery is then charged at 7.2mA, and after the upper limit voltage reaches 4.2V, it is charged at a constant voltage until the total charging time is 12 hours. Next, it is discharged at a constant current of 7.2mA until the lower limit voltage reaches 2.5V. Then, it is charged again under the same conditions, left in a 45°C constant temperature bath for 3 days, discharged again under the same conditions, and then charged and discharged one more time under the same conditions. At this time, the capacity and average voltage during the final discharge are measured. Next, after the final discharge, the thickness of the lithium-ion secondary battery is measured. Next, based on the above measurements, the electrode area of ​​the electrode laminate, the thickness of the laminate outer casing, the thickness of the negative electrode current collector, and the thickness of the positive electrode current collector in the positive electrode, the cell-equivalent energy density E (Wh / L) is calculated using the following formula. (Energy density E) = (Capacity at the last discharge) × (Average voltage at the last discharge) / (Electrode area of ​​the electrode stack) / ((Thickness of lithium-ion secondary battery) - (Thickness of laminate casing) - (Thickness of positive electrode current collector) / 2 - (Thickness of negative electrode current collector) / 2)

[17] A negative electrode active material according to any of [1] to

[16] , wherein the amount of gas generated G measured by method 2 below is 10.0% or less. (Method 2) A slurry of the negative electrode active material is prepared by adding an appropriate amount of water to a solid component consisting of 96.9 parts by mass of the negative electrode active material, 0.1 parts by mass of single-walled carbon nanotubes, and 3.0 parts by mass of polyacrylic acid. Next, the slurry of the negative electrode active material is applied to the copper foil, which is the negative electrode current collector, so that the initial charge capacity per unit area is 4.3 mAh / cm². 2 After coating with an amount such that the negative electrode current collector and negative electrode active material layer are used, the material is dried to obtain a negative electrode laminate having the negative electrode current collector and the negative electrode active material layer. Next, the negative electrode laminate is pressed using a roll press to obtain a negative electrode laminate with a density of 1.65 g / cm³ of the negative electrode active material layer. 3The negative electrode is obtained by pressing with pressure such that the following occurs. Next, the negative electrode and lithium nickel cobalt manganese oxide (Li(Ni 0.9 Co 0.05 Mn 0.05 A lithium-ion secondary battery is manufactured by placing an electrode laminate, in which a positive electrode containing )O2) and a non-aqueous electrolyte are positioned opposite each other via a polyethylene separator, and placing the laminate laminate and a non-aqueous electrolyte inside a laminate outer casing formed by processing an aluminum-based film. Positive electrode tabs and negative electrode tabs are connected to the negative electrode and positive electrode, respectively, and the laminate outer casing is sealed. Next, the lithium-ion secondary battery is placed in a constant temperature bath at 45°C, and the charging and discharging of the lithium-ion secondary battery is repeated a total of 500 times according to the <charge-discharge cycle> described below. Next, the volume of the lithium-ion secondary battery after the first charge-discharge and after the 500th charge-discharge is measured using the Archimedes method. Next, the amount of gas generated G (%) is measured from the following formula. (Gas generation amount G) = 100 × {(Volume of lithium-ion secondary battery after 500 charge / discharge cycles) - (Volume of lithium-ion secondary battery after 1 charge / discharge cycle)} / (Volume of lithium-ion secondary battery after 1 charge / discharge cycle) <Charge-discharge cycle> The lithium-ion secondary battery is charged at 30mA until it reaches the upper voltage limit of 4.25V. Then, after reaching the upper voltage limit of 4.25V, the lithium-ion secondary battery is charged at a constant voltage until 2.5 hours have elapsed since the start of charging. Then, the lithium-ion secondary battery is discharged at a constant current of 30mA until it reaches the lower voltage limit of 2.5V.

[18] A negative electrode containing the negative electrode active material described in any of [1] to

[17] .

[19] A lithium-ion secondary battery having the negative electrode described in

[18] .

[20] A lithium-ion secondary battery module comprising the lithium-ion secondary battery described in

[19] . [Effects of the Invention]

[0008] According to the present invention, it is possible to provide a negative electrode active material and a negative electrode that can be used to obtain a lithium-ion secondary battery with an improved balance of rapid charging characteristics, energy density, and gas generation suppression, as well as a lithium-ion secondary battery and a lithium-ion secondary battery module with an improved balance of rapid charging characteristics, energy density, and gas generation suppression. [Brief explanation of the drawing]

[0009] [Figure 1] This is a schematic cross-sectional view illustrating an example of a lithium-ion secondary battery according to this embodiment. [Modes for carrying out the invention]

[0010] Embodiments of the present invention will be described in detail below with reference to the drawings. To avoid complexity, if there are multiple identical components in the same drawing, a reference numeral may be assigned to only one of them, and not to all of them. The drawings are for illustrative purposes only. The shapes and dimensional ratios of the components shown in the drawings do not necessarily correspond to those of actual items.

[0011] In this embodiment, "A~B" indicating a numerical range means A or greater and B or less, unless otherwise specified.

[0012] <Negative electrode active material> The negative electrode active material of this embodiment comprises graphite powder and Si / C powder containing Si-C composite particles containing silicon and carbon material, wherein the graphite powder comprises graphite powder (A) and graphite powder (B), and the fracture strength of graphite powder (A), measured in accordance with JIS R 1639-5:2007, is CS A The fracture strength of the graphite powder (B) is CS B In that case, CS A <CS B And CS B / CS A The value is between 3.00 and 6.20.

[0013] According to our investigations, in a negative electrode active material containing graphite powder and Si / C powder containing Si-C composite particles including silicon and carbon materials, we found that there is a correlation between the ratio of the fracture strengths of the two types of graphite powder contained in the graphite powder and the balance of performance in rapid charging characteristics, energy density, and gas generation suppression of the resulting lithium-ion secondary battery.

[0014] Based on the above findings, the inventors conducted further studies and found that the present invention comprises graphite powder and Si / C powder containing Si-C composite particles containing silicon and carbon materials, and the graphite powder is such that the fracture strength of graphite powder (A), measured in accordance with JIS R 1639-5:2007, is CS A The fracture strength of graphite powder (B) is CS B In that case, CS A <CS B CS B / CS A We discovered that by setting the value of to 3.00 or more and 6.20 or less, the balance of performance in rapid charging characteristics, energy density, and gas generation suppression of the resulting lithium-ion secondary battery can be improved, thus completing the present invention.

[0015] The CS of the negative electrode active material of this embodiment B / CS A The value of is 3.00 to 6.20, preferably 3.20 to 6.15, more preferably 3.40 to 6.10, even more preferably 3.60 to 6.05, even more preferably 3.80 to 6.00, and even more preferably 4.00 to 6.00, from the viewpoint of further improving the performance balance of rapid charging characteristics, energy density, and gas generation suppression of the resulting lithium-ion secondary battery.

[0016] In the negative electrode active material of this embodiment, CS AFrom the viewpoint of further improving the balance of performance in terms of rapid charging characteristics, energy density, and gas generation suppression of the resulting lithium-ion secondary battery, the pressure is preferably 5 MPa to 50 MPa, more preferably 8 MPa to 40 MPa, even more preferably 10 MPa to 35 MPa, even more preferably 12 MPa to 30 MPa, even more preferably 14 MPa to 25 MPa, and even more preferably 15 MPa to 22 MPa.

[0017] In the negative electrode active material of this embodiment, CS B From the viewpoint of further improving the balance of performance in rapid charging characteristics, energy density, and gas generation suppression of the resulting lithium-ion secondary battery, the pressure is preferably 30 MPa to 200 MPa, more preferably 40 MPa to 170 MPa, even more preferably 50 MPa to 150 MPa, even more preferably 55 MPa to 130 MPa, and even more preferably 60 MPa to 110 MPa.

[0018] In this embodiment, the fracture strength of graphite powder and Si / C powder can be measured, for example, by the following method in accordance with JIS R 1639-5:2007. First, the test force P(N) at which particles in the powder break is measured using a microcompression tester with an indenter. Specifically, after sprinkling a minute amount of powder onto the sample stage, 100 arbitrary particles are compressed one by one with an indenter, and the test force P(N) at which particles in the powder break is determined. The particle diameter d(mm) of each particle is measured in two orthogonal directions (X and Y directions in the observation image of the microcompression tester), and the average value is taken. Next, the breaking strength CS of each particle is calculated from the test force P(N), particle diameter d(mm), and pi (π) using the following formula, and the average value of the breaking strength CS for 100 particles is taken as the breaking strength of the powder. CS = 2.48 × P / (π × d 2 )

[0019] In this embodiment, methods for adjusting the fracture strength of graphite powder and Si / C powder include, for example, using commercially available graphite powder and Si / C powder with different fracture strengths, or adjusting the manufacturing conditions of graphite powder and Si / C powder, such as surface treatment and heat treatment, to produce graphite powder and Si / C powder with different fracture strengths.

[0020] <Graphite powder (A)> The graphite powder (A) of this embodiment preferably contains graphite particles that do not contain amorphous carbon on their surface, from the viewpoint of further improving the balance of performance in rapid charging characteristics, energy density, and gas generation suppression of the resulting lithium-ion secondary battery.

[0021] The graphite powder (A) of this embodiment preferably contains artificial graphite particles, from the viewpoint of further improving the balance of performance in rapid charging characteristics, energy density, and gas generation suppression of the resulting lithium-ion secondary battery.

[0022] Median diameter D in the volume frequency particle size distribution of graphite powder (A) of this embodiment as determined by laser diffraction scattering 50 From the viewpoint of further improving the balance of performance in rapid charging characteristics, energy density, and gas generation suppression of the resulting lithium-ion secondary battery, the particle size is preferably 0.5 μm to 30.0 μm, more preferably 1.0 μm to 25.0 μm, even more preferably 3.0 μm to 20.0 μm, even more preferably 5.0 μm to 15.0 μm, and even more preferably 7.0 μm to 12.0 μm.

[0023] In this embodiment, the following methods can be used to measure the volume frequency particle size distribution of graphite powder and Si / C powder. First, the powder is suspended in a dispersion medium and dispersed using ultrasonic waves. Next, the volume frequency particle size distribution of the powder is measured using a laser diffraction particle size distribution analyzer by laser diffraction scattering. Five measurements are performed, and the average value can be used.

[0024] In this embodiment, the content of graphite powder (A) in the negative electrode active material is preferably 5.0 parts by mass or more and 60.0 parts by mass or less, more preferably 10.0 parts by mass or more and 50.0 parts by mass or less, even more preferably 15.0 parts by mass or more and 45.0 parts by mass or less, and even more preferably 18.0 parts by mass or more and 42.0 parts by mass or less, when the total amount of negative electrode active material is 100.0 parts by mass, from the viewpoint of further improving the balance of performance of the rapid charging characteristics, energy density and gas generation suppression of the resulting lithium-ion secondary battery.

[0025] <Graphite powder (B)> In this embodiment, the graphite powder (B) preferably contains graphite particles with amorphous carbon on its surface, from the viewpoint of further improving the balance of performance in rapid charging characteristics, energy density, and gas generation suppression of the resulting lithium-ion secondary battery.

[0026] The graphite powder (B) of this embodiment preferably contains artificial graphite particles, from the viewpoint of further improving the balance of performance in terms of rapid charging characteristics, energy density, and gas generation suppression of the resulting lithium-ion secondary battery.

[0027] Median diameter D in the volume frequency particle size distribution of graphite powder (B) of this embodiment as determined by laser diffraction scattering 50 From the viewpoint of further improving the balance of performance in rapid charging characteristics, energy density, and gas generation suppression of the resulting lithium-ion secondary battery, the particle size is preferably 1.0 μm to 50.0 μm, more preferably 3.0 μm to 40.0 μm, even more preferably 5.0 μm to 30.0 μm, even more preferably 7.0 μm to 25.0 μm, even more preferably 8.0 μm to 20.0 μm, and even more preferably 9.0 μm to 17.0 μm.

[0028] In this embodiment, the content of graphite powder (B) in the negative electrode active material is preferably 10.0 parts by mass or more and 80.0 parts by mass or less, more preferably 15.0 parts by mass or more and 70.0 parts by mass or less, even more preferably 20.0 parts by mass or more and 65.0 parts by mass or less, even more preferably 25.0 parts by mass or more and 60.0 parts by mass or less, and even more preferably 28.0 parts by mass or more and 58.0 parts by mass or less, when the total amount of negative electrode active material is 100.0 parts by mass, from the viewpoint of further improving the balance of performance of the rapid charging characteristics, energy density and gas generation suppression of the resulting lithium-ion secondary battery.

[0029] The content of graphite powder (A) in the negative electrode active material of this embodiment is W A The content of graphite powder (B) in the negative electrode active material of this embodiment is W B When that happens, W B / W A From the viewpoint of further improving the balance of performance in rapid charging characteristics, energy density, and gas generation suppression of the resulting lithium-ion secondary battery, the value of is preferably 0.50 to 3.00, more preferably 0.60 to 2.80, even more preferably 0.70 to 2.60, even more preferably 0.80 to 2.50, and even more preferably 0.90 to 2.40.

[0030] <Graphite powder> The graphite powder of this embodiment preferably includes artificial graphite particles, from the viewpoint of further improving the balance of performance in rapid charging characteristics, energy density, and gas generation suppression of the resulting lithium-ion secondary battery.

[0031] In this embodiment, the amount of graphite powder in the negative electrode active material is preferably 10.0 parts by mass or more and 99.0 parts by mass or less, more preferably 20.0 parts by mass or more and 97.0 parts by mass or less, even more preferably 30.0 parts by mass or more and 95.0 parts by mass or less, even more preferably 40.0 parts by mass or more and 90.0 parts by mass or less, and even more preferably 45.0 parts by mass or more and 85.0 parts by mass or less, when the total amount of negative electrode active material is 100.0 parts by mass.

[0032] These graphite powders can be obtained by, for example, subjecting commercially available graphite powder to classification treatment using a sieve having an appropriate opening ratio and wire diameter, to adjust the median diameter D 50 and the like. The graphite powder containing graphite particles with amorphous carbon on the surface can be obtained, for example, by coating 2 to 5 parts by weight of amorphous carbon on 100 parts by weight of commercially available graphite powder through methods such as arc ion plating, sputtering, and plasma CVD. At this time, the fracture strength of the graphite powder can be adjusted by adjusting the thickness of the amorphous carbon coating layer. Examples of commercially available graphite powders include graphite powders manufactured by Nippon Graphite Industry Co., Ltd., and graphite powders manufactured by JFE Chemical Corporation.

[0033] <Si / C Powder> The Si / C powder of the present embodiment includes Si-C composite particles containing silicon and a carbon material. In the Si / C powder of the present embodiment, preferably, the carbon material in the Si-C composite particles includes a porous carbon material, and silicon is present in at least a part of the pores of the porous carbon material.

[0034] In the present embodiment, as a method for confirming that the Si-C composite particles in the Si / C powder contain silicon and a carbon material, and that silicon is present in at least a part of the pores of the porous carbon material in the Si-C composite particles, for example, for the cross section of the Si-C composite particles in the Si / C powder, using a scanning electron microscope, an energy dispersive X-ray spectroscopy detector and image analysis software, selecting secondary electrons as the detection target, performing elemental mapping of silicon and carbon under the conditions of an acceleration voltage of 3 kV, a mapping integration count of 20 times, and a magnification of 3000 times, and conducting observation, may be mentioned.

[0035] Examples of porous carbon materials that constitute Si-C composite particles include activated carbon, aggregates of carbon fibers or carbon nanotubes, carbon obtained by heat treatment of resins or organic materials, and hard carbon. Porous carbon materials can be produced by known manufacturing methods such as activated carbon production methods or heat treatment of polymers, but they can also be purchased commercially, and are not limited to these methods as long as silicon can be produced or incorporated into the pores of the porous carbon.

[0036] The fracture strength of the Si / C powder of this embodiment, as measured in accordance with JIS R 1639-5:2007, is preferably 50 MPa to 600 MPa, more preferably 100 MPa to 550 MPa, even more preferably 150 MPa to 500 MPa, even more preferably 200 MPa to 450 MPa, and even more preferably 220 MPa to 420 MPa, from the viewpoint of further improving the balance of performance in rapid charging characteristics, energy density, and gas generation suppression of the resulting lithium-ion secondary battery.

[0037] Median diameter D in the volume frequency particle size distribution of Si / C powder according to the laser diffraction scattering method of this embodiment 50 From the viewpoint of further improving the balance of performance in rapid charging characteristics, energy density, and gas generation suppression of the resulting lithium-ion secondary battery, the particle size is preferably 0.5 μm to 30.0 μm, more preferably 1.0 μm to 25.0 μm, even more preferably 3.0 μm to 20.0 μm, even more preferably 5.0 μm to 15.0 μm, and even more preferably 7.0 μm to 10.0 μm.

[0038] In this embodiment, the Si / C powder content in the negative electrode active material is preferably 1.0 parts by mass or more and 90.0 parts by mass or less, more preferably 3.0 parts by mass or more and 80.0 parts by mass or less, even more preferably 5.0 parts by mass or more and 70.0 parts by mass or less, even more preferably 10.0 parts by mass or more and 60.0 parts by mass or less, and even more preferably 15.0 parts by mass or more and 55.0 parts by mass or less, when the total amount of the negative electrode active material is 100.0 parts by mass, from the viewpoint of further improving the balance of performance in rapid charging characteristics, energy density and gas generation suppression of the resulting lithium-ion secondary battery.

[0039] The content of graphite powder in the negative electrode active material of this embodiment is W C The content of Si / C powder in the negative electrode active material of this embodiment is W SiC When that happens, W SiC / W C From the viewpoint of further improving the balance of performance in rapid charging characteristics, energy density, and gas generation suppression of the resulting lithium-ion secondary battery, the value of is preferably 0.10 to 10.00, more preferably 0.15 to 5.00, even more preferably 0.18 to 3.00, even more preferably 0.20 to 2.00, and even more preferably 0.20 to 1.50.

[0040] In this embodiment, the method for producing Si / C powder is not particularly limited, but for example, a median diameter of 0.5 to 30.0 μm and a specific surface area of ​​700 to 2500 m² may be used. 2 This material can be obtained by a manufacturing method in which porous carbon material in a tubular furnace is placed, the furnace is purged with argon gas, a mixed gas of silane gas and nitrogen gas containing 1-3 mol% silane gas is flowed into the furnace at a flow rate of 150-500 sccm, and the furnace is maintained at 450-550°C, 700-800 Torr, and the process is carried out for 90-150 minutes.

[0041] <Energy density E> The energy density E measured by the following Method 1 of the present embodiment is, from the viewpoint of further improving the energy density of the obtained lithium ion secondary battery, in terms of cell conversion, preferably 875 Wh / L or higher, more preferably 880 Wh / L or higher, and even more preferably 885 Wh / L or higher. The upper limit of the energy density E is not particularly limited, and may be, for example, 1500 Wh / L or lower, 1200 Wh / L or lower, or 1000 Wh / L or lower. (Method 1) An appropriate amount of water is added to a solid content consisting of 96.9 parts by mass of a negative electrode active material, 0.1 parts by mass of single-walled carbon nanotubes, and 3.0 parts by mass of polyacrylic acid, to prepare a negative electrode active material slurry. Next, the negative electrode active material slurry is applied onto a copper foil that is a negative electrode current collector, such that the initial charge capacity per unit area is 4.3 mAh / cm 2 After applying at a coating amount that achieves the above, the coating is dried to obtain a negative electrode laminate having a negative electrode current collector and a negative electrode active material layer. Next, using a roll press machine, the negative electrode laminate is pressed at a pressure such that the density of the negative electrode active material layer is 1.65 g / cm 3 to obtain a negative electrode. Next, the negative electrode and lithium nickel cobalt manganese oxide (Li(Ni 0.9 Co 0.05 Mn 0.05A lithium-ion secondary battery is fabricated by placing an electrode laminate, in which a positive electrode containing O2 is positioned opposite a polyethylene separator, and a non-aqueous electrolyte inside a laminate casing molded from an aluminum-based film, connecting positive and negative electrode tabs to the negative and positive electrodes respectively, and sealing the perimeter of the laminate casing. Next, the lithium-ion secondary battery is charged at 7.2mA, and after the upper voltage limit reaches 4.2V, it is charged at a constant voltage until the total charging time is 12 hours. Next, it is discharged at a constant current of 7.2mA until the lower voltage limit reaches 2.5V. Then, it is charged again under the same conditions, left in a 45°C constant temperature bath for 3 days, discharged again under the same conditions, and then charged and discharged one more time under the same conditions. At this time, the capacity and average voltage during the final discharge are measured. Next, after the final discharge, the thickness of the lithium-ion secondary battery is measured. Next, based on the above measurements, the electrode area of ​​the electrode stack, the thickness of the laminate casing, the thickness of the negative electrode current collector, and the thickness of the positive electrode current collector in the positive electrode, the cell-equivalent energy density E (Wh / L) is calculated using the following formula. (Energy density E) = (Capacity at the last discharge) × (Average voltage at the last discharge) / (Electrode area of ​​the electrode stack) / ((Thickness of lithium-ion secondary battery) - (Thickness of laminate casing) - (Thickness of positive electrode current collector) / 2 - (Thickness of negative electrode current collector) / 2)

[0042] The energy density E measured by method 1 of this embodiment may be, for example, 875 Wh / L or more and 1500 Wh / L or less, 880 Wh / L or more and 1200 Wh / L or less, or 885 Wh / L or more and 1000 Wh / L or less, on a cell basis.

[0043] <Gas generation amount G> The amount of gas generated G measured by the method 2 described below in this embodiment is preferably 10.0% or less, more preferably 9.0% or less, even more preferably 8.0% or less, even more preferably 7.0% or less, and even more preferably 6.0% or less, from the viewpoint of further suppressing the amount of gas generated in the resulting lithium-ion secondary battery. The lower limit of the amount of gas generated G is not particularly limited, but for example it may be 0.1% or more, 1.0% or more, 2.0% or more, or 3.0% or more. (Method 2) A slurry of negative electrode active material is prepared by adding an appropriate amount of water to a solid component consisting of 96.9 parts by mass of negative electrode active material, 0.1 parts by mass of single-walled carbon nanotubes, and 3.0 parts by mass of polyacrylic acid. Next, the slurry of negative electrode active material is applied to the copper foil, which is the negative electrode current collector, to achieve an initial charge capacity of 4.3 mAh / cm² per unit area. 2 After coating with an appropriate amount, the material is dried to obtain a negative electrode laminate having a negative electrode current collector and a negative electrode active material layer. Next, using a roll press machine, the negative electrode laminate is processed so that the density of the negative electrode active material layer is 1.65 g / cm³. 3 The negative electrode is obtained by pressing with pressure such that the following occurs. Next, the negative electrode and lithium nickel cobalt manganese oxide (Li(Ni 0.9 Co 0.05 Mn 0.05 A lithium-ion secondary battery is fabricated by placing an electrode stack, in which a positive electrode containing )O2) and a non-aqueous electrolyte are positioned opposite each other via a polyethylene separator, inside a laminated casing molded from an aluminum-based film, connecting positive electrode tabs and negative electrode tabs to the negative electrode and positive electrode respectively, and sealing the perimeter of the laminated casing. Next, the lithium-ion secondary battery is placed in a 45°C constant temperature bath, and the charging and discharging of the lithium-ion secondary battery is repeated a total of 500 times according to the <charge-discharge cycle> described below. Then, the volume of the lithium-ion secondary battery after the first charge-discharge and after the 500th charge-discharge is measured using the Archimedes method. Next, the amount of gas generated G (%) is measured from the following formula. (Gas generation amount G) = 100 × {(Volume of lithium-ion secondary battery after 500 charge / discharge cycles) - (Volume of lithium-ion secondary battery after 1 charge / discharge cycle)} / (Volume of lithium-ion secondary battery after 1 charge / discharge cycle) <Charge-discharge cycle> The lithium-ion secondary battery is charged at 30mA until it reaches the upper voltage limit of 4.25V. Then, after reaching the upper voltage limit of 4.25V, the lithium-ion secondary battery is charged at a constant voltage until 2.5 hours have elapsed since the start of charging. Next, the lithium-ion secondary battery is discharged at a constant current of 30mA until it reaches the lower voltage limit of 2.5V.

[0044] The amount of gas generated G measured by method 2 of this embodiment may be, for example, 0.1% or more and 10.0% or less, 0.1% or more and 9.0% or less, 1.0% or more and 8.0% or less, 2.0% or more and 7.0% or less, or 3.0% or more and 6.0% or less.

[0045] <Negative electrode> The negative electrode of this embodiment includes the negative electrode active material of this embodiment. The negative electrode of this embodiment preferably comprises a negative electrode active material layer containing the negative electrode active material of this embodiment and a negative electrode current collector, from the viewpoint of further improving the battery performance of the resulting lithium-ion secondary battery. The negative electrode active material layer of this embodiment preferably contains the negative electrode active material and binder of this embodiment, and more preferably contains the negative electrode active material, binder and conductive additive of this embodiment, from the viewpoint of further improving the battery performance of the resulting lithium-ion secondary battery.

[0046] From the viewpoint of further improving the balance of performance in rapid charging characteristics, energy density, and gas generation suppression of the resulting lithium-ion secondary battery, the content of the negative electrode active material in the negative electrode active material layer of this embodiment is preferably 50.0 parts by mass or more and 100.0 parts by mass or less, more preferably 75.0 parts by mass or more and 99.9 parts by mass or less, even more preferably 85.0 parts by mass or more and 99.5 parts by mass or less, even more preferably 90.0 parts by mass or more and 99.0 parts by mass or less, even more preferably 95.0 parts by mass or more and 98.5 parts by mass or less, and even more preferably 96.0 parts by mass or more and 98.0 parts by mass or less, when the total amount of the negative electrode active material layer is 100.0 parts by mass.

[0047] Examples of conductive additives in the negative electrode active material layer of this embodiment include carbon fibers such as carbon nanofibers; carbon blacks such as acetylene black and Ketjen black; and carbon materials such as activated carbon, mesoporous carbon, fullerenes, and carbon nanotubes. One of these may be used alone, or two or more may be used in combination. Among these, the conductive additive in the negative electrode active material layer of this embodiment preferably contains a carbon material, more preferably contains carbon nanotubes, and even more preferably contains single-walled carbon nanotubes, from the viewpoint of further improving the battery performance of the resulting lithium-ion secondary battery.

[0048] From the viewpoint of further improving the battery performance of the resulting lithium-ion secondary battery, the content of the conductive additive in the negative electrode active material layer of this embodiment is preferably 0.01 parts by mass or more and 5.0 parts by mass or less, more preferably 0.03 parts by mass or more and 1.0 part by mass or less, even more preferably 0.05 parts by mass or more and 0.5 parts by mass or less, and even more preferably 0.07 parts by mass or more and 0.3 parts by mass or less, when the total amount of the negative electrode active material layer is 100.0 parts by mass.

[0049] Examples of binders in the negative electrode active material layer of this embodiment include fluororesins such as polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), and polyvinyl fluoride (PVF); polycarboxylic acid polymers such as poly(meth)acrylic acid; conductive polymers such as polyaniline, polythiophene, polyacetylene, and polypyrrole; synthetic rubbers such as styrene-butadiene rubber (SBR), butadiene rubber (BR), chloroprene rubber (CR), isoprene rubber (IR), and acrylonitrile-butadiene rubber (NBR); and polysaccharides such as carboxymethylcellulose (CMC), xanthan gum, guar gum, and pectin. One of these may be used alone, or two or more may be used in combination. Among these, the binder in the negative electrode active material layer of this embodiment preferably contains one or more selected from the group consisting of fluororesin, polycarboxylic acid polymer, and synthetic rubber, from the viewpoint of further improving the battery performance of the resulting lithium-ion secondary battery, more preferably contains one or more selected from the group consisting of polyvinylidene fluoride, polycarboxylic acid polymer, and styrene-butadiene rubber, even more preferably contains a polycarboxylic acid polymer, and even more preferably contains poly(meth)acrylic acid.

[0050] From the viewpoint of further improving the battery performance of the resulting lithium-ion secondary battery, the binder content in the negative electrode active material layer of this embodiment is preferably 0.1 parts by mass or more and 10.0 parts by mass or less, more preferably 1.0 parts by mass or more and 7.0 parts by mass or less, and even more preferably 2.0 parts by mass or more and 5.0 parts by mass or less, when the total amount of the negative electrode active material layer is 100.0 parts by mass.

[0051] In this embodiment, the thickness of the negative electrode active material layer is preferably 10 μm to 250 μm, more preferably 20 μm to 200 μm, and even more preferably 50 μm to 150 μm, from the viewpoint of further improving the battery performance of the resulting lithium-ion secondary battery.

[0052] The density of the negative electrode active material layer of the present embodiment is, from the viewpoint of further improving the battery performance of the obtained lithium ion secondary battery, preferably 0.50 g / cm 3 or more and 3.00 g / cm 3 or less, more preferably 1.00 g / cm 3 or more and 2.50 g / cm 3 or less, still more preferably 1.30 g / cm 3 or more and 2.00 g / cm 3 or less.

[0053] The negative electrode current collector of the present embodiment may be formed of, for example, copper, stainless steel, nickel, titanium, or an alloy thereof. The shape of the negative electrode current collector may be, for example, a foil, a flat plate, or a mesh. The thickness of the negative electrode current collector is not particularly limited, and is, for example, 1 μm or more and 50 μm or less.

[0054] <Lithium Ion Secondary Battery> The lithium ion secondary battery of the present embodiment includes the negative electrode of the present embodiment. Since the lithium ion secondary battery of the present embodiment includes the negative electrode containing the negative electrode active material of the present embodiment, the performance balance of rapid charging characteristics, energy density, and suppression of gas generation amount is improved.

[0055] The lithium ion secondary battery of the present embodiment will be described with reference to the drawings. Figure 1 is a schematic cross-sectional view schematically showing an example of the lithium ion secondary battery of the present embodiment. As shown in Figure 1, the lithium ion secondary battery 10 includes the negative electrode of the present embodiment, an electrolytic solution, and a positive electrode. Further, a separator 5 can be provided between the positive electrode and the negative electrode. A plurality of electrode pairs of the positive electrode and the negative electrode can be provided.

[0056] The lithium-ion secondary battery 10 has a positive electrode comprising a positive electrode current collector 3 made of a metal such as aluminum foil and a positive electrode active material layer 1 containing a positive electrode active material provided thereon, and a negative electrode comprising a negative electrode current collector 4 made of a metal such as copper foil and a negative electrode active material layer 2 containing a negative electrode active material provided thereon. The positive electrode and the negative electrode are laminated via a separator 5 made of a nonwoven fabric or a polypropylene microporous film, for example, so that the positive electrode active material layer 1 and the negative electrode active material layer 2 face each other. This electrode pair is housed in a container formed of an outer casing 6, 7 made of an aluminum laminate film, for example. A positive electrode tab 9 is connected to the positive electrode current collector 3 and a negative electrode tab 8 is connected to the negative electrode current collector 4, and these tabs are led out of the container. An electrolyte is injected into the container and sealed. A structure in which a group of electrodes, each consisting of multiple laminated electrode pairs, is housed in the container is also possible.

[0057] The lithium-ion secondary battery 10 can be manufactured according to known methods. For electrodes, for example, laminates or wound bodies can be used. For the outer casing, metal casings or aluminum laminate casings can be used as appropriate. The shape of the battery may be any shape, such as coin type, button type, sheet type, cylindrical type, prismatic type, or flat type.

[0058] In the lithium-ion secondary battery of this embodiment, the positive electrode preferably comprises a positive electrode active material layer containing a positive electrode active material and a positive electrode current collector. The positive electrode active material layer of this embodiment preferably contains a positive electrode active material and a binder, and more preferably contains a positive electrode active material, a binder, and a conductive additive.

[0059] The positive electrode active material in the positive electrode active material layer of this embodiment may be, for example, lithium-nickel composite oxide, lithium-cobalt composite oxide, lithium-manganese composite oxide, lithium-nickel-manganese composite oxide, lithium-nickel-cobalt composite oxide, lithium-nickel-aluminum composite oxide, lithium-nickel-cobalt-aluminum composite oxide, lithium-nickel-manganese-cobalt composite oxide, lithium-nickel-manganese-aluminum composite oxide, lithium-nickel-cobalt-manganese-aluminum composite oxide, and other composite oxides of lithium and transition metals; transition metal sulfides such as TiS2, FeS, MoS2; and MnO, V2O5, V6O 13 Examples include transition metal oxides such as TiO2, and olivine-type lithium phosphate oxides. One of these may be used alone, or two or more may be used in combination.

[0060] Examples of conductive additives in the positive electrode active material layer of this embodiment include carbon fibers such as carbon nanofibers; carbon blacks such as acetylene black and Ketjenblack; and carbon materials such as activated carbon, mesoporous carbon, fullerenes, and carbon nanotubes. One of these may be used alone, or two or more may be used in combination.

[0061] Examples of binders in the positive electrode active material layer of this embodiment include fluorine-based binders such as polytetrafluoroethylene (PTFE) and polyvinylidene fluoride (PVDF); and aqueous binders such as styrene-butadiene rubber. One of these may be used alone, or two or more may be used in combination.

[0062] The positive electrode current collector of this embodiment may be made of, for example, aluminum, stainless steel, nickel, titanium, or an alloy thereof. The shape of the positive electrode current collector may be, for example, foil, a flat plate, or a mesh. The thickness of the positive electrode current collector is not particularly limited, but for example, it is 1 μm or more and 50 μm or less.

[0063] Examples of electrolytes in this embodiment include cyclic carbonates such as ethylene carbonate (EC), propylene carbonate (PC), vinylene carbonate (VC), and butylene carbonate (BC); linear carbonates such as ethyl methyl carbonate (EMC), diethyl carbonate (DEC), dimethyl carbonate (DMC), and dipropyl carbonate (DPC); aliphatic carboxylic acid esters; γ-lactones such as γ-butyrolactone; linear ethers; and cyclic ethers, in which lithium salts such as lithium hexafluoride phosphate (LiPF6), lithium borofluoride (LiBF4), LiFSI, and lithium perchlorate (LiClO4) are dissolved. The organic solvent may be used alone or in combination of two or more.

[0064] The separator of this embodiment is, for example, mainly made of a porous membrane, woven fabric, nonwoven fabric, etc., and as the resin component, for example, polyolefin resins such as polypropylene and polyethylene, polyester resins, acrylic resins, styrene resins, or nylon resins can be used. In addition, if necessary, a layer containing inorganic particles may be formed in the separator, and examples of inorganic particles include insulating oxides, nitrides, sulfides, carbides, etc.

[0065] As the outer casing of this embodiment, for example, a case or can made of a flexible film can be used, and from the viewpoint of reducing the weight of the battery, it is preferable to use a flexible film. The flexible film can be one in which a resin layer is provided on both the front and back surfaces of a metal base layer. The metal layer can be selected to have barrier properties such as preventing leakage of electrolyte and intrusion of moisture from the outside, and can be made of aluminum, stainless steel, etc. A heat-sealable resin layer, such as a modified polyolefin, is provided on at least one surface of the metal layer. The outer casing is formed by facing the heat-sealable resin layers of the flexible film toward each other and heat-sealing the area around the part that houses the electrode laminate. A resin layer such as a nylon film or polyester film can be provided on the surface of the outer casing opposite to the surface on which the heat-sealable resin layer is formed.

[0066] <Lithium-ion secondary battery module> The lithium-ion secondary battery module of this embodiment comprises the lithium-ion secondary battery of this embodiment. Since the lithium-ion secondary battery of this embodiment has an improved balance of performance in terms of rapid charging characteristics, energy density, and gas generation suppression, the lithium-ion secondary battery module of this embodiment has an improved balance of performance in terms of rapid charging characteristics, energy density, and gas generation suppression.

[0067] The lithium-ion secondary battery module of this embodiment preferably includes two or more lithium-ion secondary batteries of this embodiment connected in series or in parallel. The lithium-ion secondary battery module of this embodiment more preferably includes a housing capable of housing two or more lithium-ion secondary batteries of this embodiment connected in series or in parallel. The lithium-ion secondary battery module of this embodiment more preferably includes one or more selected from the group consisting of a protection circuit to protect the lithium-ion secondary batteries from overcurrent, a balance circuit to equalize the voltage between the electrodes of the lithium-ion secondary batteries, a controller to control the lithium-ion secondary batteries, a cooler capable of cooling the lithium-ion secondary batteries, and a heater capable of heating the lithium-ion secondary batteries.

[0068] The lithium-ion secondary battery module of this embodiment can be used in a battery system comprising multiple electrically connected lithium-ion secondary battery modules and a battery control system. Examples of battery systems include battery packs, stationary battery systems, automotive power battery systems, automotive auxiliary battery systems, and emergency power supply battery systems.

[0069] Although embodiments of the present invention have been described above, these are merely examples, and various other configurations can be adopted. Furthermore, the present invention is not limited to the embodiments described above, and modifications and improvements that can achieve the objectives of the present invention are included within the scope of the present invention. [Examples]

[0070] Embodiments of the present invention will be described in detail based on Examples and Comparative Examples. The present invention is not limited to the Examples alone.

[0071] <Preparation of Si / C Powder 1> Porous carbon material 1 (D 50 : 8.0 μm, specific surface area: 1200 m 2 / g) was placed in a tubular furnace, the inside of the tubular furnace was purged with argon gas, then a mixed gas of 2 mol% silane gas and 98 mol% nitrogen gas was flowed into the tubular furnace at a flow rate of 300 sccm, and the treatment was performed by holding under conditions of 500°C, 760 Torr, and 120 minutes. Subsequently, the product was cooled to room temperature, and Si / C Powder 1 was obtained.

[0072] For the cross section of the Si-C composite particles contained in the obtained Si / C Powder 1, using a scanning electron microscope (manufactured by Hitachi High-Tech Corporation, SU3500), an energy dispersive X-ray spectroscopic analysis detector (manufactured by Oxford Instruments, Ultim Max 40) and image analysis software (manufactured by Oxford Instruments, Aztec), secondary electrons were selected as the detection target, and elemental mapping of silicon and carbon was performed under conditions of an acceleration voltage of 3 kV, a mapping integration count of 20 times, and a magnification of 3000 times, and it was confirmed that the Si-C composite particles contain silicon, and in the Si-C composite particles, silicon is present in at least a part of the pores of the porous carbon material.

[0073] <Preparation of Si / C Powder 2 and Si / C Powder 3> Si / C Powder 2 was produced in the same manner as Si / C Powder 1, except that Porous carbon material 2 (D 50 : 8.0 μm, specific surface area: 2000 m 2 / g) was used in place of Porous carbon material 1, and the flow rate of the mixed gas was set to 400 sccm, and Si / C Powder 3 was produced in the same manner as Si / C Powder 1, except that Porous carbon material 3 (D 50 : 5.0 μm, specific surface area: 900 m 2 / g) was used in place of Porous carbon material 1, and the flow rate of the mixed gas was set to 250 sccm.

[0074] Elemental mapping was performed on the cross-sections of the Si-C composite particles contained in the obtained Si / C powder 2 and Si / C powder 3 using the same method as described for Si / C powder 1. It was confirmed that in both cases, the Si-C composite particles contained silicon, and that silicon was present in at least a portion of the pores of the porous carbon material within the Si-C composite particles.

[0075] The fracture strength of each Si / C powder was measured in accordance with JIS R 1639-5:2007. Specifically, first, the test force P(N) at which Si / C powder particles break was measured using an indenter with a microcompression tester (Shimadzu Corporation, MCT-510). That is, after sprinkling a minute amount of Si / C powder on the sample stage, 100 arbitrary particles were compressed one by one with an indenter, and the test force P(N) at which the Si / C powder particles break was determined. The particle diameter d(mm) of each particle was measured in two orthogonal directions (X and Y directions in the observation image of the microcompression tester), and the average value was taken. Next, the breaking strength CS of each particle was calculated from the test force P(N), particle diameter d(mm), and pi π using the following formula, and the average breaking strength CS of 100 particles was taken as the breaking strength of the Si / C powder. CS = 2.48 × P / (π × d 2 ) The results showed that the fracture strength of Si / C powder 1 was 280 MPa, the fracture strength of Si / C powder 2 was 400 MPa, and the fracture strength of Si / C powder 3 was 230 MPa.

[0076] For each Si / C powder, the median diameter D is determined from the volume frequency particle size distribution measured by laser diffraction scattering using a laser diffraction particle size distribution analyzer (SALD-2300, Shimadzu Corporation). 50 The volume frequency particle size distribution was determined by suspending the Si / C powder in a dispersion medium (0.1% by mass sodium hexametaphosphate aqueous solution), ultrasonically dispersing it, and then measuring it. Five measurements were taken, and the average value was used for each measurement. The result was the median diameter D of Si / C powder 1. 50 The median diameter D of Si / C powder 2 is 8.0 μm. 50The median diameter D of Si / C powder 3 is 8.0 μm. 50 The size was 5.0 μm.

[0077] For each Si / C powder, the specific surface area was determined using the BET flow method and the single-point method in accordance with JIS Z 8830:2013. The result showed that the specific surface area of ​​Si / C powder 1 was 2.1 m². 2 The specific surface area of ​​Si / C powder 2 is 7.0 m² / g. 2 The specific surface area of ​​Si / C powder 3 is 4.6 m² / g. 2 It was / g.

[0078] The following graphite powders were used in the preparation of the negative electrode active material.

[0079] <Graphite powder> • Graphite powder 1 (artificial graphite that does not contain amorphous carbon on the surface, breaking strength: 20 MPa, D 50 :9.9μm, specific surface area: 1.8m 2 / g) • Graphite powder 2 (artificial graphite containing amorphous carbon on the surface, breaking strength: 95 MPa, D 50 :13.4μm, specific surface area: 1.4m 2 / g) • Graphite powder 3 (artificial graphite that does not contain amorphous carbon on the surface, breaking strength: 16 MPa, D 50 :9.6μm, specific surface area: 1.5m 2 / g) • Graphite powder 4 (artificial graphite containing amorphous carbon on the surface, breaking strength: 65 MPa, D 50 :14.7μm, specific surface area: 0.8m 2 / g) • Graphite powder 5 (artificial graphite containing amorphous carbon on the surface, breaking strength: 100 MPa, D 50 :10.1μm, specific surface area: 1.0m 2 / g) • Graphite powder 6 (artificial graphite that does not contain amorphous carbon on the surface, breaking strength: 40 MPa, D 50 :9.0μm, specific surface area: 1.8m 2 / g)

[0080] Fracture strength and median diameter D of each graphite powder50 The specific surface area was determined using the same measurement method as for Si / C powder.

[0081] <Fabrication of negative electrode active material> The graphite powder and Si / C powder were mixed in the proportions shown in Table 1 to obtain the negative electrode active materials for Examples 1-11 and Comparative Examples 1-2.

[0082] <Fabrication of the negative electrode> For each example and comparative example, a negative electrode active material slurry was prepared by adding an appropriate amount of water to a solid component consisting of 96.9 parts by mass of negative electrode active material, 0.1 parts by mass of single-walled carbon nanotubes, and 3.0 parts by mass of polyacrylic acid. Next, the negative electrode active material slurry was applied to an 8 μm thick copper foil, which served as the negative electrode current collector, with an initial charge capacity of 4.3 mAh / cm² per unit area. 2 After coating with an amount such that the following conditions were met, the material was dried to obtain a negative electrode laminate having a negative electrode current collector and a negative electrode active material layer. Next, using a roll press machine, the negative electrode laminate was processed so that the density of the negative electrode active material layer was 1.65 g / cm³. 3 The negative electrodes for each embodiment and each comparative example were obtained by pressing with a pressure such that the electrodes were pressed.

[0083] <Fabrication of the positive electrode> Lithium nickel cobalt manganese oxide (Li(Ni 0.9 Co 0.05 Mn 0.05 A cathode active material slurry was prepared by adding an appropriate amount of N-methyl-2-pyrrolidone to a solid component consisting of 97.5 parts by mass of O2, 1.5 parts by mass of polyvinylidene fluoride, and 1.0 part by mass of single-walled carbon nanotubes. Next, the cathode active material slurry was applied to a 12 μm thick aluminum foil, which serves as the cathode current collector, to achieve an initial charge capacity of 4.0 mAh / cm² per unit area. 2 After coating with an amount such that the positive electrode current collector and positive electrode active material layer were obtained by drying, a positive electrode laminate having a positive electrode current collector and a positive electrode active material layer was obtained. Next, using a roll press machine, the positive electrode laminate was rolled so that the density of the positive electrode active material layer was 3.5 g / cm³. 3 The positive electrode was obtained by pressing it with a pressure such that it would result in a positive electrode.

[0084] <Preparation of non-aqueous electrolyte> The non-aqueous electrolyte was prepared by mixing an organic solvent with a supporting salt. The cyclic carbonate ethylene carbonate and the linear carbonate ethylmethyl carbonate were adjusted to a volume ratio of 3 / 7. Furthermore, lithium hexafluoride phosphate (LiPF6) (concentration: 1.2 mol / L) was used as the supporting salt, and fluoroethylene carbonate (concentration relative to the organic solvent: 6% by mass) was used as an additive.

[0085] <Manufacturing of lithium-ion secondary batteries> The positive electrode and the negative electrode of each example and comparative example were cut to 3 cm x 3 cm and placed opposite each other with a separator in between to create an electrode laminate. A 10 μm thick microporous polyethylene film coated with ceramic on both sides was used as the separator. Next, the electrode laminate and the non-aqueous electrolyte were placed inside a laminate casing molded from a film mainly composed of aluminum, and positive electrode tabs and negative electrode tabs were connected to the negative electrode and positive electrode, respectively. The lithium-ion secondary batteries of each example and comparative example were then fabricated by sealing the periphery of the laminate casing. Here, one end of the positive electrode tab is connected to the positive electrode and the other end is led out of the casing, and one end of the negative electrode tab is connected to the negative electrode and the other end is led out of the casing.

[0086] <Quick charging characteristics> For each example and comparative example, the lithium-ion secondary battery was charged to a State of Charge (SOC) of 50% under conditions of 25°C and a charge rate of 3.0C, and then discharged to a SOC of 0% under conditions of 25°C and a discharge rate of 0.1C. Next, the charged and discharged lithium-ion secondary batteries were disassembled, and the deposition of lithium on the negative electrode surface was visually confirmed. Then, the rapid charging characteristics of the lithium-ion secondary batteries were evaluated based on the following criteria. The results are shown in Table 1. A: When charged to 50% SOC, lithium does not deposit on the surface of the negative electrode. B: When charged to 50% SOC, lithium deposits form on the surface of the negative electrode.

[0087] <Energy density E> For each example and comparative example of lithium-ion secondary battery, charging was performed at 7.2mA, and after the upper voltage limit reached 4.2V, charging was performed at a constant voltage until the total charging time was 12 hours. Next, the battery was discharged at a constant current of 7.2mA until the lower voltage limit reached 2.5V. Then, it was charged again under the same conditions, left in a constant temperature bath at 45°C for 3 days, discharged again under the same conditions, and then charged and discharged one more time under the same conditions. During this process, the capacity and average voltage at the time of the final discharge were measured. Next, the thickness of the lithium-ion secondary battery was measured after the final discharge. Then, based on the above measurements, the electrode area of ​​the electrode stack, the thickness of the laminate casing, the thickness of the negative electrode current collector, and the thickness of the positive electrode current collector, the cell-equivalent energy density E (Wh / L) was calculated using the following formula. The results are shown in Table 1. (Energy density E) = (Capacity at the last discharge) × (Average voltage at the last discharge) / (Electrode area of ​​the electrode stack) / ((Thickness of lithium-ion secondary battery) - (Thickness of laminate casing) - (Thickness of positive electrode current collector) / 2 - (Thickness of negative electrode current collector) / 2)

[0088] <Gas generation amount G> For each example and comparative example, the lithium-ion secondary battery was placed in a constant temperature bath at 45°C, and the charging and discharging of the lithium-ion secondary battery was repeated a total of 500 times according to the <charge-discharge cycle> described below. Then, the volume of the lithium-ion secondary battery was measured using the Archimedes method after the first charge-discharge cycle and after the 500th charge-discharge cycle. Next, the amount of gas generated G (%) was measured using the following formula. The results are shown in Table 1. (Gas generation amount G) = 100 × {(Volume of lithium-ion secondary battery after 500 charge / discharge cycles) - (Volume of lithium-ion secondary battery after 1 charge / discharge cycle)} / (Volume of lithium-ion secondary battery after 1 charge / discharge cycle) <Charge-discharge cycle> The lithium-ion secondary battery was charged at 30mA until it reached its upper voltage limit of 4.25V. Then, after reaching the upper voltage limit of 4.25V, the lithium-ion secondary battery was charged at a constant voltage until 2.5 hours had elapsed since the start of charging. Next, the lithium-ion secondary battery was discharged at a constant current of 30mA until it reached its lower voltage limit of 2.5V.

[0089] [Table 1]

[0090] As can be seen from Table 1, in the negative electrode active material, the capacity and gas generation tend to increase as the ratio of Si / C powder to graphite powder increases. However, it can be seen that the rapid charging characteristics, energy density, and gas generation are also affected by the type of graphite powder and Si / C powder used. In particular, it can be seen that the fracture strength of the graphite powder affects the rapid charging characteristics, energy density, and gas generation. [Explanation of Symbols]

[0091] 1 Cathode active material layer 2 Negative electrode active material layer 3 Positive electrode current collector 4 Negative electrode current collector 5 Separators 6. Exterior 7. Exterior 8 Negative Electrode Tabs 9 Positive Tab 10 Lithium-ion rechargeable batteries

Claims

1. The mixture comprises graphite powder and Si / C powder containing Si-C composite particles containing silicon and carbon materials. The graphite powder comprises graphite powder (A) and graphite powder (B), The fracture strength of the graphite powder (A), measured in accordance with JIS R 1639-5:2007, is CS A The fracture strength of the graphite powder (B) is CS B In that case, CS A <CS B And CS B / CS A A negative electrode active material whose value is between 3.00 and 6.

20.

2. Said CS A The negative electrode active material according to claim 1, wherein the pressure is 5 MPa or more and 50 MPa or less.

3. Said CS B The negative electrode active material according to claim 1 or 2, wherein the pressure is 30 MPa or more and 200 MPa or less.

4. The negative electrode active material according to any one of claims 1 to 3, wherein the graphite powder (A) contains graphite particles that do not have amorphous carbon on their surface.

5. The negative electrode active material according to any one of claims 1 to 4, wherein the graphite powder (B) contains graphite particles having amorphous carbon on their surface.

6. The content of the graphite powder (A) in the negative electrode active material is defined as W A , the content of the graphite powder (B) in the negative electrode active material is defined as W B , the negative electrode active material according to any one of claims 1 to 5, wherein the value of W B / W A is 0.50 or more and 3.00 or less.

7. Median diameter D in the volume frequency particle size distribution of the graphite powder (A) obtained by laser diffraction scattering method. 50 The negative electrode active material according to any one of claims 1 to 6, wherein the particle size is 0.5 μm or more and 30.0 μm or less.

8. Median diameter D in the volume frequency particle size distribution of the graphite powder (B) obtained by laser diffraction scattering method 50 The negative electrode active material according to any one of claims 1 to 7, wherein the particle size is 1.0 μm or more and 50.0 μm or less.

9. The negative electrode active material according to any one of claims 1 to 8, wherein the graphite powder contains artificial graphite particles.

10. The negative electrode active material according to any one of claims 1 to 9, wherein the content of the graphite powder in the negative electrode active material is 10.0 parts by mass or more and 99.0 parts by mass or less when the total amount of the negative electrode active material is 100.0 parts by mass.

11. The negative electrode active material according to any one of claims 1 to 10, wherein the carbon material in the Si-C composite particles includes a porous carbon material, and the silicon is present in at least a portion of the pores of the porous carbon material.

12. The negative electrode active material according to any one of claims 1 to 11, wherein the fracture strength of the Si / C powder, as measured in accordance with JIS R 1639-5:2007, is 50 MPa or more and 600 MPa or less.

13. Median diameter D in the volume frequency particle size distribution of the Si / C powder obtained by laser diffraction scattering method. 50 The negative electrode active material according to any one of claims 1 to 12, wherein the particle size is 0.5 μm or more and 30.0 μm or less.

14. The negative electrode active material according to any one of claims 1 to 13, wherein the content of the Si / C powder in the negative electrode active material is 1.0 part by mass or more and 90.0 parts by mass or less when the total amount of the negative electrode active material is 100.0 parts by mass.

15. The content of the graphite powder in the negative electrode active material is W C The content of the Si / C powder in the negative electrode active material is W SiC When that happens, W SiC / W C The negative electrode active material according to any one of claims 1 to 14, wherein the value of is 0.10 or more and 10.00 or less.

16. The negative electrode active material according to any one of claims 1 to 15, wherein the energy density E measured by the method 1 below is 875 Wh / L or more on a cell basis. (Method 1) A slurry of the negative electrode active material is prepared by adding an appropriate amount of water to a solid component consisting of 96.9 parts by mass of the negative electrode active material, 0.1 parts by mass of single-walled carbon nanotubes, and 3.0 parts by mass of polyacrylic acid. Next, the slurry of the negative electrode active material is applied to the copper foil, which is the negative electrode current collector, so that the initial charge capacity per unit area is 4.3 mAh / cm². 2 After applying the coating in an amount such that the negative electrode current collector and the negative electrode active material layer are dried to obtain a negative electrode laminate having the negative electrode current collector and the negative electrode active material layer. Next, the negative electrode laminate is pressed using a roll press to obtain a negative electrode laminate with a density of 1.65 g / cm³ of the negative electrode active material layer. 3 The negative electrode is obtained by pressing with a pressure such that the negative electrode is then subjected to lithium nickel cobalt manganese oxide (Li(Ni) 0.9 Co 0.05 Mn 0.05 ) O 2 A lithium-ion secondary battery is manufactured by placing an electrode laminate, in which a positive electrode containing a ) and a non-aqueous electrolyte are arranged opposite each other via a polyethylene separator, and placing the laminate laminate and a non-aqueous electrolyte inside a laminate outer casing molded from an aluminum-based film, connecting positive electrode tabs and negative electrode tabs to the negative electrode and positive electrode respectively, and sealing the periphery of the laminate outer casing. Next, the lithium-ion secondary battery is charged at 7.2 mA, and after the upper limit voltage reaches 4.2 V, it is charged at a constant voltage until the total charging time is 12 hours. Next, it is discharged at a constant current of 7.2 mA until the lower limit voltage reaches 2.5 V. Next, it is charged again under the same conditions, left in a constant temperature bath at 45°C for 3 days, discharged again under the same conditions, and then charged and discharged one more time under the same conditions. At this time, the capacity and average voltage at the time of the last discharge are measured. Next, after the last discharge, the thickness of the lithium-ion secondary battery is measured. Next, based on the above measurements, the electrode area of ​​the electrode laminate, the thickness of the laminate casing, the thickness of the negative electrode current collector, and the thickness of the positive electrode current collector in the positive electrode, the cell-equivalent energy density E (Wh / L) is calculated using the following formula. (Energy density E) = (Capacity at the last discharge) × (Average voltage at the last discharge) / (Electrode area of ​​the electrode stack) / ((Thickness of lithium-ion secondary battery) - (Thickness of laminate casing) - (Thickness of positive electrode current collector) / 2 - (Thickness of negative electrode current collector) / 2)

17. The negative electrode active material according to any one of claims 1 to 16, wherein the amount of gas generated G measured by the method 2 below is 10.0% or less. (Method 2) A slurry of the negative electrode active material is prepared by adding an appropriate amount of water to a solid component consisting of 96.9 parts by mass of the negative electrode active material, 0.1 parts by mass of single-walled carbon nanotubes, and 3.0 parts by mass of polyacrylic acid. Next, the slurry of the negative electrode active material is applied to the copper foil, which is the negative electrode current collector, so that the initial charge capacity per unit area is 4.3 mAh / cm². 2 After applying the coating in an amount such that the negative electrode current collector and the negative electrode active material layer are dried to obtain a negative electrode laminate having the negative electrode current collector and the negative electrode active material layer. Next, the negative electrode laminate is pressed using a roll press to obtain a negative electrode laminate with a density of 1.65 g / cm³ of the negative electrode active material layer. 3 The negative electrode is obtained by pressing with a pressure such that the negative electrode is then subjected to lithium nickel cobalt manganese oxide (Li(Ni) 0.9 Co 0.05 Mn 0.05 ) O 2 A lithium-ion secondary battery is manufactured by placing an electrode laminate, in which a positive electrode containing a ) and a non-aqueous electrolyte are arranged opposite each other via a polyethylene separator, and placing the laminate laminate and a non-aqueous electrolyte inside a laminate outer casing formed by processing an aluminum-based film, connecting positive electrode tabs and negative electrode tabs to the negative electrode and positive electrode respectively, and sealing the periphery of the laminate outer casing. Next, the lithium-ion secondary battery is placed in a constant temperature bath at 45°C, and the charging and discharging of the lithium-ion secondary battery is repeated a total of 500 times according to the <charge-discharge cycle> described below. Next, the volume of the lithium-ion secondary battery after the first charge-discharge and after the 500th charge-discharge is measured using the Archimedes method. Next, the amount of gas generated G (%) is measured from the following formula. (Gas generation amount G) = 100 × {(Volume of lithium-ion secondary battery after 500 charge / discharge cycles) - (Volume of lithium-ion secondary battery after 1 charge / discharge cycle)} / (Volume of lithium-ion secondary battery after 1 charge / discharge cycle) <Charge / Discharge Cycle> The lithium-ion secondary battery is charged at 30 mA until it reaches an upper voltage limit of 4.25 V. Then, after reaching the upper voltage limit of 4.25 V, the lithium-ion secondary battery is charged at a constant voltage until 2.5 hours have elapsed since the start of charging. Then, the lithium-ion secondary battery is discharged at a constant current of 30 mA until it reaches a lower voltage limit of 2.5 V.

18. A negative electrode comprising the negative electrode active material according to any one of claims 1 to 17.

19. A lithium-ion secondary battery comprising the negative electrode described in claim 18.

20. A lithium-ion secondary battery module comprising the lithium-ion secondary battery described in claim 19.

Citation Information

Patent Citations

  • Composite particles, their production method and uses

    JP2023059283A